Penyelesaian Sengketa Kredit Macet pada BMT El Ummu Rahimah Kabupaten Sijunjung Sumatera Barat - arnes, okto viandra arnes; Arianti, Farida (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
Baitul Maal wa Tamwil (BMT) is one of the financial institutions engaged in financial services based on sharia principles in carrying out its activities. However, Baitul maal wa tamwil is not uncommon or frequent bad credit disputes committed by customers intentionally or unintentionally. This research is quantitative research, namely field research by exploring data sourced from BMT El Ummu Rahimah Sijunjung Regency, West Sumatra regarding dispute resolution in Baitul Maal Wa Tamwil. The data collected uses field research (Field Research), namely collecting data through interviews, observations and other materials. In resolving bad credit disputes at Baitul maal wa tamwil, there are alternative solutions that must be taken by customers, namely through litigation (in court) and non-litigation (out of court). However, the settlement of bad credit disputes at BMT El Ummu Rahimah is resolved in a non-litigation manner, namely dispute resolution outside the court. There are several steps taken by BMT El Ummu Rahimah in resolving bad credit disputes, namely giving warning letters, providing relief and the existence of settlements made amicably in the event of bad credit by customers. But what is no less important is that BMT El Ummu Rahimah is unable to return the customer's money. So that BMT El Ummu Rahimah was audited and all of its goods were confiscated.